Pure Red Cell Aplasia and Other Haematological Diseases Associated With Thymoma: A Case Series and Systematic Review - Yen, Chih-Chieh; Huang, Wei-Li; Li, Sin-Syue; Chen, Ya-Ping; Tseng, Yau-Lin; Yen, Yi-Ting; Chu, Chang-Yao; Hsu, Ya-Ting; Chen, Tsai-Yun (Frontiers in Medicine, 2021)
Background: Thymoma-associated haematological diseases (HDs), such as pure red cell aplasia (PRCA) and Good’s syndrome, are extremely rare, and due to the paucity of large-scale studies, the characteristics, remission after thymectomy and long-term evaluation remain undetermined. Methods: We retrospectively assessed patients with thymoma and associated HDs from Jan 2005 to Dec 2020. All patients received thymectomy and/or additional treatments for HDs. A comparison with thymoma-associated myasthenic gravis (MG), and a systematic review from PubMed/MEDLINE and Embase were conducted. Results: In the median follow-up of 56 months, 130 patients were enrolled. Patients with thymoma-associated MG (n=46) and HDs (n=8; PRCA (n=5), PRCA and Good’s syndrome (n=2) and autoimmune haemolytic anaemia (n=1)) were evaluated. Patients with MG had a significantly higher remission rate after thymectomy (50% vs. 17%; p=0.0378) as compared to those with other autoimmune diseases. Two of seven patients with PRCA experienced remission with thymectomy alone, and an additional two patients achieved remission with thymectomy plus immunosuppressive therapy (IST). In the systematic review, 60 studies (case reports, n=46; case series including the present study, n=14) were evaluated. Forty-four percent of patients were diagnosed with PRCA after thymoma, and 61% achieved remission with thymectomy plus IST; however, Good’s syndrome was unaffected. Conclusions: Our study indicates that patients with thymoma-associated autoimmune diseases other than MG have a lower remission rate than those with MG. Remission of thymoma-associated PRCA can be achieved by thymectomy and IST. This study provides insight into extremely rare but puzzling autoimmune manifestations.